Does TikTok Social Media Increase Public Interest in the Seafarer Profession? - Mashudi Rofik; Ahmad Narto (Indonesian Institute For Counseling, Education and Therapy, 2026)
Background: The rise of TikTok videos showing life and work at sea has increased public exposure to the seafarer profession. Many seafarers actively share their experiences on board ships, creating wider professional visibility. However, previous studies mainly discuss TikTok as a platform for entertainment and promotion, while limited studies examine its role in influencing career interest in the maritime profession. This creates a research gap regarding how TikTok shapes public motivation toward becoming seafarers. Objective: This study aims to investigate the influence of TikTok social media on public interest in the seafarer profession. Methods: This study uses a mixed-method approach with concurrent quantitative and qualitative analysis. Quantitative data were collected through questionnaires distributed via Microsoft Teams to students participating in level 1 and level 2 seafarer training in Semarang. From a population of 126 participants, 95 respondents were selected based on the Krejcie and Morgan table with a 95% confidence level. Qualitative data were obtained through in-depth interviews and TikTok content analysis. Results: The results show a significant positive relationship between TikTok exposure and interest in the seafarer profession (Pearson correlation = 0.936; p < 0.001), indicating a strong association between maritime-related content consumption and career interest. Qualitative findings show that educational content, visual attractiveness, and influencer narratives increase motivation, while occupational risks and incomplete professional representation remain important barriers. Conclusion: TikTok plays an important role as a strategic medium for career visibility and professional promotion in the maritime sector, although the findings indicate correlation rather than direct causality.